New and rare lichens and allied fungi from Arkhangelsk region, North-West Russia - Tarasova, Viktoria; Konoreva, Liudmila; Zhurbenko, Mikhail; Pystina, Tatiana; Chesnokov, Sergei; Androsova, Vera; Sonina, Angella; Semenova, Natalia; Valekzhanin, Andrei (Folia Cryptogamica Estonica, 2020)
Thirty-one lichen-forming fungi, 12 lichenicolous fungi, and 5 non-lichenized fungi are reported as new for Arkhangelsk Region; 7 species are new for its mainland area. Micarea fallax is reported for the first time for Russia; M. laeta and M. pusilla are new for the European part of Russia. The second finding of Nicropuncta rugulosa for Russia is recorded; microconidia are first observed in this species. The records of ten species which have been included in the new edition of the Red Data Book of the Arkhangelsk Region (2020) are presented. Nephromopsis laureri from the Red Data Book of the Russian Federation (2008) and Leptogium rivulare from the IUCN Red List are reported for the first time for Arkhangelsk Region.